Horizon 474 - A new winter oat cultivar for both grain and forage - Ann Blount; Ronald Barnett; Jerry Johnson; Cheryl Mackowiak; Yoana Newman (EDIS)
SS-AGR-281, a 2-page fact sheet by Ann Blount, Ronald Barnett, Jerry Johnson, Cheryl Mackowiak, and Yoana Newman, describes this oat cultivar, considered to be an excellent choice for grain, hat, grazing, or ensiling in the southeastern U.S. Published by the UF Department of Agronomy, October 2007.